Shear bond strength of three diferent bonding systems for orthodontic brackets - Lon, Luís Filipe Siu [UNESP]; Knop, Luegya Amorim Henriques [UNESP]; Shintcovsk, Ricardo Lima [UNESP]; Filho, Odilon Guariza; Raveli, Dirceu Barnabé [UNESP] (Universidade Estadual de Campinas, 2018)
Aim: The objective of this study was to compare the efficiencies of different adhesive systems used to bond orthodontic brackets as well as the fracture pattern during debonding on bovine teeth. Methods: The sample included 45 specimens assigned to 3 groups according to the adhesive system applied: Group I: Transbond XT (3M Unitek®, Monrovia/CA - USA), Group II: Orthocem (FGM® Joinville/ SC-BR), and Group III: Orthobond (Morelli®, Sorocaba/SP - BR). For this purpose, metal brackets were bonded to bovine teeth following the instructions from each manufacturer. The specimens were subjected to a shear test to assess bond strength (BS). Finally, after debonding, the adhesive remnant index (ARI) was estimated. Results: The average shear strength for a tooth bonded using the adhesive system Transbond XT was 16.39 MPa, while it was 18.08 Mpa for Orthocem and 7.28 Mpa for Orthobond; The Tukey test revealed no statistically significant differences between groups I and II (p < 0.01) and group III differed statistically from groups I and II. Conclusion: In conclusion, both adhesive systems Transbond XT and Orthocem attained higher bond strength values than Orthobond; the fracture pattern was similar for all adhesive systems applied.
Keywords: Dental bonding; Dental enamel; Shear strength